1952
DOI: 10.1182/blood.v7.3.326.326
|View full text |Cite
|
Sign up to set email alerts
|

Certain Endocrine Influences Governing the Leukocytic Response to Fever

Abstract: A study is reported of the influences exerted on the levels of the circulating eosinophils, lymphocytes and neutrophils of rats in which body temperatures have been elevated for one hour to 41.0 or to 41.5 C. by means of the Raytheon microwave diathermy apparatus. Preliminary studies were made to determine the influence exerted on these blood categories by the restrictions imposed on the animals such as confinement in cages and insertion of rectal thermistors: factors incident to the experimental procedure. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1953
1953
1970
1970

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There are certain alterations in circulating leucocytes, usually mild leucopenia followed by leucocytosis, in artificial fever (42)(43)(44)(45)(46)(47); that these are of any particular significance in resistance is not evident at present. Some claims for increased phagocytic power of the leucocytes from febrile man or animals are based on trivial changes or are unfounded (48).…”
Section: Effects Of Fever Upon the Hostmentioning
confidence: 99%
“…There are certain alterations in circulating leucocytes, usually mild leucopenia followed by leucocytosis, in artificial fever (42)(43)(44)(45)(46)(47); that these are of any particular significance in resistance is not evident at present. Some claims for increased phagocytic power of the leucocytes from febrile man or animals are based on trivial changes or are unfounded (48).…”
Section: Effects Of Fever Upon the Hostmentioning
confidence: 99%
“…Any stress upon an animal which might effect the adrenal cortex or medulla could thus be expected to produce eosino penia, lymphpenia, and neutrophilia. Hubler et al (1952) reported that immobilization of rats in a plastic cage for the purpose of collecting blood samples resulted in neutrophilia, lymphopenia and eosinopenia. The lymphocytes dropped to of their initial values within one hour.…”
Section: Sesponse To Inflabhiiationmentioning
confidence: 99%